-22-4r=6(3+6r)

Simple and best practice solution for -22-4r=6(3+6r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22-4r=6(3+6r) equation:


Simplifying
-22 + -4r = 6(3 + 6r)
-22 + -4r = (3 * 6 + 6r * 6)
-22 + -4r = (18 + 36r)

Solving
-22 + -4r = 18 + 36r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-36r' to each side of the equation.
-22 + -4r + -36r = 18 + 36r + -36r

Combine like terms: -4r + -36r = -40r
-22 + -40r = 18 + 36r + -36r

Combine like terms: 36r + -36r = 0
-22 + -40r = 18 + 0
-22 + -40r = 18

Add '22' to each side of the equation.
-22 + 22 + -40r = 18 + 22

Combine like terms: -22 + 22 = 0
0 + -40r = 18 + 22
-40r = 18 + 22

Combine like terms: 18 + 22 = 40
-40r = 40

Divide each side by '-40'.
r = -1

Simplifying
r = -1

See similar equations:

| 3(1[3u-3]1)+3(1[2u-4]1)=x | | (4x^5+3x-12)-(3x^3+x-3x-7)= | | 2x-3y-8z+-3x+5y-11z= | | 16+28x-4=180 | | 16+18x-4=180 | | 37x=73 | | 2=-2(1+2)-4(x+5) | | 65x+100=55x-100 | | -28=7(p+3)+3(8p-6) | | 65x+100=55x | | 8x^3-12x^2-6x+9=0 | | 7+8c=7 | | 4x+4y+(-9x)= | | 0=-3x-1+y | | 55x=65x+100 | | 6m+5m-3m=7(m-1) | | 12=-4(1+2n) | | 23.5x+14.75y=739.25 | | 2x+10=7(x-1) | | -3x=6.6 | | 12x-4=-3-(-x) | | 4=-4(3+x) | | log^7(4x+9)=2 | | -(a-2)-6a-2=21 | | -8=8(-2x-7) | | -3x-1.2=5.4 | | -6x=-25 | | 1+2x-4=3-(-x) | | -6x=-253 | | x-2=2+2 | | 125x^3=8 | | x/30=30/150 |

Equations solver categories